-3(X+6)+4=-23

Simple and best practice solution for -3(X+6)+4=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(X+6)+4=-23 equation:


Simplifying
-3(X + 6) + 4 = -23

Reorder the terms:
-3(6 + X) + 4 = -23
(6 * -3 + X * -3) + 4 = -23
(-18 + -3X) + 4 = -23

Reorder the terms:
-18 + 4 + -3X = -23

Combine like terms: -18 + 4 = -14
-14 + -3X = -23

Solving
-14 + -3X = -23

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -3X = -23 + 14

Combine like terms: -14 + 14 = 0
0 + -3X = -23 + 14
-3X = -23 + 14

Combine like terms: -23 + 14 = -9
-3X = -9

Divide each side by '-3'.
X = 3

Simplifying
X = 3

See similar equations:

| 12(t-6)+3t=5(3t+3)-11 | | 2x^2-12x+30=0 | | 3t^2-24t+30=0 | | 5+2(v+2)=3(v+7) | | 3(x+5)=-9 | | 124-p=628 | | (Y-25)+x=180 | | X^2=11-x | | 12(3x-4)=3(12x+2) | | -4x^2-9x-6=0 | | -(6x-4)=-4(x+6) | | (4+2n^3)+(5n^3+2)=0 | | -(7y+3)-(-6y-4)=-3 | | 3+3m-1=9m+6-5m | | 3(5X+4)-10X+9=51 | | 17+3y=5 | | Y-25=180 | | -2(x-8)+9=25 | | Y-25+x+52+96=360 | | -5-3b=4(b+4) | | x+2x+4=10 | | X+52+96=180 | | 26-2a=-2(6a+3)+2 | | y=1.5x-0.4 | | 4(2x+1)-3x=34 | | 3s+8=-9s | | 5x^5=20x^3 | | 2x^2-15x+27=0 | | 4x+2*8=9*4x | | -2(7r+1)-6=-64 | | 2x^2-7x+9=x+1 | | -7.5x=15.0 |

Equations solver categories